Intensity modulated radiotherapy (IMRT) + carbon ion boost for adenoid cystic carcinoma of the minor salivary glands in the oral cavity - Uzun-Lang, Kristin; Baur, Melissa; Akbaba, Sati; Held, Thomas; Kargus, Steffen; Bougatf, Nina; Bernhardt, Denise; Freier, Kolja; Plinkert, Peter K.; Rieken, Stefan; Debus, Jürgen; Adeberg, Sebastian (Cancers, 2018)
Background: Adenoid cystic carcinoma (ACC) are more common in the minor salivary glands (MiSGs) than the major salivary glands, and are characterized by slow tumor progression and frequently local recurrence. The main treatment option is surgery followed by combined radiotherapy. Methods: A retrospective analysis contained 67 patients with ACC of MiSGs in the oral cavity who underwent surgery followed by radiotherapy. The median cumulative IMRT dose was 50 Gy followed by 24 Gy for carbon ion (C12) boost. Median follow-up was 40 months. Results: Median 5-years overall survival (OS), progression-free survival (PFS) and local disease-free survival (LDFS) rates were 85.5%, 57.4% and 74.9%. Median time until progression was detected was 32 months (range: 2–205 months). Early grade ≥3 mucositis, dermatitis, and dysphagia were detected in 52.2%, 7.5% and 11.9% respectively. Besides common toxicities, two patients (3.0%) developed grade 3 toxicities with osteoradionecrosis of the jaw after 18 and 66 months. Higher-grade late toxicity (CTCAE grade 4) was not detected. No treatment-related death was detected. Conclusions: Our results demonstrate that postoperative combined radiotherapy with IMRT plus C12 boost seems to be a feasible and effective treatment method in ACC of MiSGs in the oral cavity, with good control and survival rates and adequate toxicity.
Gesehen am 04.11.2019